"The Needs of Consumers Oblige": Daily Problems and Criticism of the System in Public Letters in the 1960s and 1980s - Reet Ruusmann (Journal of Ethnology and Folkloristics)
This article examines public letters as an expression of everyday household problems and practices. The sources used are those letters from among the archival materials of the Tartu Retail Trade Association and the Tallinn Markets Administration that have survived from the 1960s and 1980s. Using qualitative thematic analysis, I examine the points of criticism that have arisen in connection with retail trade and the (deficit) reality behind it, along with specific behavioural practices. In addition, my aim is to show the relations between individuals and the state, and their dynamics, by presenting criticism with the help of discourse analysis.